THE EFFECT OF STRESS ON STUDYING AND ORGANISATIONAL PROCESSES (American Journal of Pedagogical and Educational Research, 2022)
Nowadays, an awful lot of people strive to maintain up with the current responsibilities, tasks, as well as to challenge distinguishing prospective opportunities and threats. Modern-based living and working conditions tend to dictate own terms and even take a control of individuals having them obsessed with their work and personal responsibilities. Thus, people of different age and background often have an emotional problem and tempt stress issues in work. However, such behavior and emotional conditions are basically reflected in working performance and attaining organizational goals.